Tissue culture and morphogenesis of Begonia x Hiemalis fotsch. cv.Schwabenland Red / Asmah Awal - Awal, Asmah (2009)
In vitro regeneration of Begonia x hiemalis Fotsch. cv. Schwabenland Red, also known as Begonia Rose, an ornamental plant was achieved from four different intact explants; such as leaf, peduncle, petiole and stem explants. The sterilization protocol was established for in vivo explants to overcome contamination. The results revealed that four different types of explants could produce in vitro regeneration. Leaf and petiole explants were amongst the best explants that were observed in this study. The optimum regeneration medium was identified in this study, i.e. MS medium supplemented with 1.0 mg/l BAP and 1.0 mg/l NAA which produced normal shoots. Treatment of MS medium supplemented with lower concentration of BAP (0.1 mg/l) and NAA (0.1 mg/l) produced less normal shoots, whereas higher concentration of BAP (2.0 mg/l) and NAA (2.0 mg/l) produced micro shoots. No shoot could be obtained in the MS media devoid of hormone and also in MS supplemented with various concentrations of BAP applied singly. Root induction were obtained in the MS medium supplemented with various concentrations of NAA and MS media fortified with 0.5-1.0 mg/l NAA could produce optimum root induction. TDZ is known to have high cytokinin-like activity was identified as effective in the production of abnormal micro shoots, whereas combinations of different types of auxins and cytokinins could also produce in vitro shoots. Optimization of callus induction was also established in Begonia. Two different types of explants were selected in this study i.e. leaf and petiole explants. Optimum callus could be obtained in MS supplemented with 1.0 mg/l BAP and 0.5 mg/l 2,4-D. Green and yellowish, compact nodular callus were obtained during callus induction. Treatment of x MS media fortified with different concentrations of 2,4-D (0.1-1.0 mg/l) produced yellowish nodular callus, whereas green nodular callus were obtained in MS media with combinations of BAP (1.0 mg/l) and 2,4-D (0.1-0.5 mg/l). Direct somatic embryos was also induced from leaf and petiole explants of Begonia. The stock explants derived from in vitro plantlets that were subcultured into MS media supplemented with 1.0 mg/l TIBA. By using MS solid media supplemented with 1.0 mg/l BAP, 0.1 mg/l 2,4-D and 500 mg/l casien hydrolysate, green nodular callus were induced from the explants. The nodullar structures from leaf explants were further developed into heart-shaped, torpedo-shaped and cotyledonary-stage upon transferred to development media (MS media supplemented with 0.5 mg/l GA3). The optimum callus produced in Begonia was further cultured into suspension cultures to mass-produce the callus. The results showed that embryogenic callus could multiply in the MS liquid media supplemented with 1.0 mg/l BAP in combination with 0.1 mg/l 2, 4-D. A new protocol was identified to propagate callus for regeneration purposes. The suspension cultures containing cotyledonary-stage structures were subcultured onto MS solid media supplemented with 0.5 mg/l GA3 for further development of the embryoids. In this study, production of synthetic seeds was also attempted. Somatic embryos and micro shoots were encapsulated in 3.0% (w/v) of sodium alginate solution for the production of synthetic seeds. The synthetic seeds which were stored at 4 °C for 1-6 months were successfully germinated onto MS basal media. The germination rate was up to 83.33%. The synthetic seeds were also successfully germinated under in vivo conditions on topsoil 1 and vermiculite but not on the sphagnum. xi In vitro flowering was also investigated in Begonia using three different explants i.e. inflorescences, peduncles and petals. The results obtained showed that in vitro flowering could be obtained from inflorescence explants cultured onto MS media supplemented with 1.0 mg/l BAP, 1.0 mg/l NAA, 40 mg/l adenine and 4.0% (w/v) sucrose. The abnormal red inflorescences obtained devoid of reproductive organs and did not develop into mature flowers upon transfer to MS media supplemented with 0.5 mg/l GA3. All regenerated plantlets obtained from several tissue culture techniques including in vitro regeneration, suspension cultures, somatic embryos, synthetic seeds and in vitro flowering were transferred to the greenhouse for further development. Four different types of substrates were used in this study. The results showed that topsoil 1, topsoil 2 and sphagnum could be used as substrates. Almost all regenerants produced flowers after 9 months being transplanted in the greenhouse. However, regenerants that being acclimatized in the tissue culture room (25 ±1ºC; 16 hours light and 8 hours dark) did not produce flowers even after 12 months of incubation period. SEM and some morphological studies proved that all regenerants derived from in vitro culture systems were morphologically similar with intact (parent) plant of Begonia x hiemalis Fotsch. cv. Schwabenland Red.